2015
DOI: 10.3382/ps/pev273
|View full text |Cite
|
Sign up to set email alerts
|

Age and adaptation to Ca and P deficiencies: 2. Impacts on amino acid digestibility and phytase efficacy in broilers

Abstract: A total of 1,152 straight-run hatchling Heritage 56M×fast feathering Cobb 500F broiler birds were used to determine Ca, age, and adaptation effects on apparent ileal digestibility of crude protein (AID of CP), amino acids (AID of AA) and phytase efficacy. Twelve treatments with 8 replicates, each were fed from 7 to 9 d (6 birds per replicate), 7 to 21 d (6 birds per replicate) and 19 to 21 d (3 birds per replicate) d of age. Diets were prepared with 3 Ca (0.65, 0.80, and 0.95%) and 2 non-phytate P, (0.20 and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…It could be concluded that the older pigs need less adaptation duration compared with the younger pigs when they are fed to a new feed. In addition, Li et al [24] reported that lower apparent ileal digestibility (AID) of CP and amino acids were observed in adapted birds (7 to 21 d) compared to unadapted birds (19 to 21 d) which were affected by dietary factors, including Ca and non-phytate P. Changing the diet of pigs requires time for the microflora and gastrointestinal tract itself to adapt to the new substrates and the new absorbable products. When an adaptation duration is sufficient for fecal inocula of pigs to reach a stable microbial composition, the digestibility of nutrients tends to be stable as well.…”
Section: Discussionmentioning
confidence: 99%
“…It could be concluded that the older pigs need less adaptation duration compared with the younger pigs when they are fed to a new feed. In addition, Li et al [24] reported that lower apparent ileal digestibility (AID) of CP and amino acids were observed in adapted birds (7 to 21 d) compared to unadapted birds (19 to 21 d) which were affected by dietary factors, including Ca and non-phytate P. Changing the diet of pigs requires time for the microflora and gastrointestinal tract itself to adapt to the new substrates and the new absorbable products. When an adaptation duration is sufficient for fecal inocula of pigs to reach a stable microbial composition, the digestibility of nutrients tends to be stable as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in broilers, Amerah et al (2014) reported that a Buttiauxella phytase dosed at 1000 FTU improved total amino acid digestibility across four different Ca: AvP ratios in feed by 12.3% vs. NC in broilers. Li et al (2015) observed that addition of Buttiauxella phytase at 1000 FTU/kg improved ileal dAA in broilers, by, on average, 3.1%, 5.7% and 6.9% in the diets containing 6.5, 8 and 9.5 g/kg Ca respectively. A comparison study in broilers showed that two different phytase sources, i.e.…”
Section: Journal Of Applied Animal Nutritionmentioning
confidence: 91%
“…Using different inorganic sources may also result in different AvP equivalence values. Li et al (2015) showed that using tibia ash weight or percentage as response criteria resulted in different nPP equivalence values, for example, this was estimated as 0.117% and 0.168% based on tibia ash (%) and tibia ash weight (mg/tibia) respectively with addition of 500 FTU/kg phytase. In addition, dietary composition such as Ca level can have a great impact on the P equivalence.…”
Section: Journal Of Applied Animal Nutritionmentioning
confidence: 99%
“…The Ca requirement in modern broilers has been recently reported ( Applegate et al., 2003 , Li et al., 2012 , Li et al., 2015 , Li et al., 2016 , Li et al., 2016 , Abdulla et al., 2017 , Kim et al., 2018b ). The heightened interest in dietary Ca-related studies is due to its effect on phytase efficacy.…”
Section: Introductionmentioning
confidence: 99%